Kreativitas Anak Usia 5-6 Tahun Melalui Permainan Lego Di Taman Kanak-Kanak Minasa Upa Makassar - Amriani, Sri Rika (ECEJ : Early Childhood Education Journal, 2023)
This study examines the creativity of children aged 5-6 years through lego games in Pasuleang II kindergarten, Takalar district. The purpose of this study is to find out how children's creativity, especially ages 5-6 years. The approach in this research is descriptive qualitative with the focus of open research, namely children's creativity through lego games with the research subject, namely children aged 5-6 years in Pasuleang II kindergarten, Takalar district with the number of students, namely 24 children with one teacher. Data collection is done through direct observation by observing how children's creativity when playing lego. The data collection through interviews was conducted with group B teachers, as well as conducting documentation by collecting the results of children's assessments in the form of portfolios. Furthermore, data analysis techniques are carried out using compensional analysis techniques which include data reduction, data presentation, and conclusion drawing. The results showed that students in Pasuleang II Kindergarten have good creativity in lego games, including children who are able to think quickly, able to adjust easily, able to think original, able to detail or elaborate, and have the skills to assess.